L-Type amino acid transporter 1 as a target for drug delivery - Puris, Elena; Gynther, Mikko; Auriola, Seppo; Huttunen, Kristiina M. (Pharmaceutical research, 2020)
Our growing understanding of membrane transporters and their substrate specificity has opened a new avenue in the field of targeted drug delivery. The L-type amino acid transporter 1 (LAT1) has been one of the most extensively investigated transporters for delivering drugs across biological barriers. The transporter is predominantly expressed in cerebral cortex, blood-brain barrier, blood-retina barrier, testis, placenta, bone marrow and several types of cancer. Its physiological function is to mediate Na+ and pH independent exchange of essential amino acids: leucine, phenylalanine, etc. Several drugs and prodrugs designed as LAT1 substrates have been developed to improve targeted delivery into the brain and cancer cells. Thus, the anti-parkinsonian drug, L-Dopa, the anti-cancer drug, melphalan and the anti-epileptic drug gabapentin, all used in clinical practice, utilize LAT1 to reach their target site. These examples provide supporting evidence for the utility of the LAT1-mediated targeted delivery of the (pro)drug. This review comprehensively summarizes recent advances in LAT1-mediated targeted drug delivery. In addition, the use of LAT1 is critically evaluated and limitations of the approach are discussed.